2009
DOI: 10.3342/ceo.2009.2.4.169
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Abilities at Ultra-High Frequency in Patients with Tinnitus

Abstract: ObjectivesTo compare tinnitus patients who have normal hearing between 250 Hz and 8 kHz with normal controls with regard to the ability of each group to hear extended high-frequency pure tone thresholds.MethodsWe enrolled 18 tinnitus patients, each of whom had a threshold of HL <25 dB and threshold differences of <10 dB between ears at frequencies of 250 and 500 Hz and 1, 2, 4, and 8 kHz. We also enrolled age- and gender-matched normal volunteers (10 ears), for each patient. Extended high frequency pure tone a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
43
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 16 publications
5
43
1
1
Order By: Relevance
“…This condition represents an uncommon finding in tinnitus patients; published reports indicate that 85-96% of the patients with tinnitus present with some level of hearing loss [König et al, 2006;Roberts et al, 2010;Ryan and Bauer, 2016;Shore et al, 2016], and only 8-10% have normal hearing [Shim et al, 2009;Modh et al, 2014;Plack et al, 2014]. However, on the one hand, the AAO classification is widely recognized and used under a clinical perspective, but on the other hand, it does not include hearing loss above 3 kHz and does not highlight asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…This condition represents an uncommon finding in tinnitus patients; published reports indicate that 85-96% of the patients with tinnitus present with some level of hearing loss [König et al, 2006;Roberts et al, 2010;Ryan and Bauer, 2016;Shore et al, 2016], and only 8-10% have normal hearing [Shim et al, 2009;Modh et al, 2014;Plack et al, 2014]. However, on the one hand, the AAO classification is widely recognized and used under a clinical perspective, but on the other hand, it does not include hearing loss above 3 kHz and does not highlight asymmetry.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous study of 18 patients who showed normal hearing in PTA up to 8 kHz, 12 patients (66.7%) with tinnitus experienced a higher hearing threshold on the affected side in the extended high-frequency band compared with that in a control group of the same age and sex [Shim et al, 2009]; therefore, it is necessary to test PTA beyond 8 kHz to obtain an exact diagnosis of somatic tinnitus. For this reason, patients included in the ST group were only those with symmetric hearing ability (within 10 dB HL difference) in whole frequency of PTA that included 10, 12, 14, 16, 18 and 20 kHz, if the hearing threshold was below 20 dB HL in both ears at less than 8 kHz.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] The severity of tinnitus commonly increases with the degree of hearing loss, and the pitch of tinnitus often coincides with the frequency of the lesion or is just below the precipitous edge of the lesion. 4,5 These findings demonstrate that damage to cochlear hair cells plays a crucial role in the pathogenesis of tinnitus.…”
Section: Introductionmentioning
confidence: 99%